2021
DOI: 10.1111/eci.13532
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac troponin and COVID‐19 severity: Results from BIOCOVID study

Abstract: Background: Myocardial injury is a common finding in COVID-19 strongly associated with severity. We analysed the prevalence and prognostic utility of myocardial injury, characterized by elevated cardiac troponin, in a large population of COVID-19 patients, and further evaluated separately the role of troponin T and I. Methods: This is a multicentre, retrospective observational study enrolling patients with laboratory-confirmed COVID-19 who were hospitalized in 32 Spanish hospitals. Elevated troponin levels wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 36 publications
2
38
0
Order By: Relevance
“…Myocardial injury is defined as the presence of at least one cardiac troponin value above the 99th percentile upper reference limit (URL) according to the Fourth Universal Definition of Myocardial Infarction ( Thygesen et al., 2018 ). Consistent with many other reports ( Lombardi et al., 2020 ; Garcia De Guadiana-Romualdo et al., 2021 ; Majure et al., 2021 ), elevated hsTnI was detected in the COVID-19 patients in our study. The mechanisms for myocardial injury in COVID-19 has not been elucidated.…”
Section: Discussionsupporting
confidence: 94%
“…Myocardial injury is defined as the presence of at least one cardiac troponin value above the 99th percentile upper reference limit (URL) according to the Fourth Universal Definition of Myocardial Infarction ( Thygesen et al., 2018 ). Consistent with many other reports ( Lombardi et al., 2020 ; Garcia De Guadiana-Romualdo et al., 2021 ; Majure et al., 2021 ), elevated hsTnI was detected in the COVID-19 patients in our study. The mechanisms for myocardial injury in COVID-19 has not been elucidated.…”
Section: Discussionsupporting
confidence: 94%
“…37 Consistent with the recent two studies of cardiac microthrombi in fatal COVID-19, 13,14 we found that the minority of COVID-19 autopsies had any focal cardiac necrosis. The infrequency of cardiac necrosis in fatal COVID-19 13,14,49 contrasts with the high prevalence, magnitude, and mortality risk of cTn elevation among critically ill COVID-19 patients, 9,48,49 even after controlling for renal dysfunction. 50,51 Our cell composition and single nuclei transcriptomic data demonstrate that SARS-CoV-2 indeed impacts cardiomyocytes, resulting in their cell death and dysfunction.…”
Section: Discussionmentioning
confidence: 94%
“…One study showed that 41 (22%) of admitted patients had myocardial injury and the mortality was similar among those with myocardial injury regardless of whether they had or did not have COVID-19 infection [47]. The included studies also examined the relationship between troponin level and mortality or the prevalence of elevated cardiac enzymes among hospitalized COVID-19 patients [35,39,41,44,51,52,54,58,61,66].…”
Section: N Resultsmentioning
confidence: 99%